FACTORS ASSOCIATED WITH PERSISTENCE OF HPV GENITAL INFECTION IN A SMALL COHORT OF ROMANIAN WOMEN - Huică, Irina (Acta Clin Croat, 2019)
The aim of the study was to assess the role of behavioral factors in persistence of human papillomavirus (HPV) genital infection. Out of a cohort of 605 women included in a study of HPV infection prevalence, 142 HPV positive women (aged 18-57) were retested after a 12-month interval. None of the patients underwent surgical treatment during that period. Selected patients were asked for a second smear for cytologic analysis and HPV genotyping. A questionnaire that included information regarding reproductive health, sexual activity and smoking status was filled-in. After 12 months, 46 of 142 (32.39%) women had persistent HPV infection, with genotypes 16 and 18 found in 27 cases. On the other hand, 17 of 142 (11.97%) women had acquired new infections replacing the baseline genotypes. In our study, smoking (OR=2.320, p=0.0330) and sexual behavior (OR=5.333, p=0.0180 for more than three sexual partners; OR=2.427, p=0.0238 for cases where the partner was involved in another sexual relationship) were associated with viral persistence, while long-term contraception did not yield statistically significant results.